2022
DOI: 10.1152/ajpheart.00534.2021
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses of the inotropic compound omecamtiv mecarbil in rat and human cardiac preparations

Abstract: Omecamtiv mecarbil (OM), a myosin activator, was reported to induce complex concentration- and species-dependent effects on contractile function and clinical studies indicated a low therapeutic index with diastolic dysfunction at concentrations above 1 µM. To further characterize effects of OM in a human context and under different preload conditions, we constructed a setup that allows isometric contractility analyses of human induced pluripotent stem cell (hiPSC)-derived engineered heart tissues (EHTs). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In such circumstances, NT-proBNP remained unchanged, whereas sST2 increased markedly in our study suggesting that passive muscle tension with OM has distinct and subtle deleterious effects in the setting of AR, not reliably assessed by modifications in NT-proBNP. Furthermore the effects of OM are concentration, time, and species-dependent [25].…”
Section: Discussionmentioning
confidence: 99%
“…In such circumstances, NT-proBNP remained unchanged, whereas sST2 increased markedly in our study suggesting that passive muscle tension with OM has distinct and subtle deleterious effects in the setting of AR, not reliably assessed by modifications in NT-proBNP. Furthermore the effects of OM are concentration, time, and species-dependent [25].…”
Section: Discussionmentioning
confidence: 99%
“…Auxotonic contractions were measured until day 60 as previously described. [22][23][24] We also used a patient-derived heterozygous MYBPC3 (MYBPC3het; UKEi070-A) and its isogenic control (MYBPC3ic; UKEi070-A-1) hiPSC lines that were previously created. 12 MYBPC3het and MYBPC3ic hiPSC-cardiomyocytes (3-4 batches of differentiation of triplicates) were transduced with AAV9-TTL or AAV9-Empty (MOI 100,000) for 10 days and treated with 100 nM endothelin-1 (ET1) or vehicle (H 2 O) the last 3 days as previously described.…”
Section: Plasmid Constructs and Aav9 Particle Productionmentioning
confidence: 99%
“…Engineered heart tissues (EHTs) are three-dimensional (3D) in vitro cellular platforms containing cardiomyocytes ( Schaaf et al, 2011 ) differentiated from human pluripotent stem cells (hPSC-cardiomyocytes) ( Yamanaka, 2007 ; Burridge et al, 2012 ) and have demonstrated potential to predict cardiac drug effects from variations in their assayable functional outputs ( Matsa et al, 2014 ; Denning et al, 2016 ; Ribeiro et al, 2019 ). In these culture platforms, interconnected hPSC-cardiomyocytes forming a beating tissue are aligned between load-bearing deflectable micropost force sensors ( Eschenhagen et al, 2012 ) and can be assayed to provide functional results on drug-induced cardiac contractile effects ( Jacob et al, 2016 ; Mannhardt et al, 2016 ; Mannhardt et al, 2017 ; Saleem et al, 2020 ; Rhoden et al, 2022 ). Despite being primarily developed to determine cardiac contractility from the deflection of microposts ( Hansen et al, 2010 ), other cardiac properties have been assayed with EHTs, such as electrophysiology ( Eder et al, 2014 ), calcium cycle ( Stoehr et al, 2014 ), and metabolism and mitochondrial function ( Rhoden et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In these culture platforms, interconnected hPSC-cardiomyocytes forming a beating tissue are aligned between load-bearing deflectable micropost force sensors ( Eschenhagen et al, 2012 ) and can be assayed to provide functional results on drug-induced cardiac contractile effects ( Jacob et al, 2016 ; Mannhardt et al, 2016 ; Mannhardt et al, 2017 ; Saleem et al, 2020 ; Rhoden et al, 2022 ). Despite being primarily developed to determine cardiac contractility from the deflection of microposts ( Hansen et al, 2010 ), other cardiac properties have been assayed with EHTs, such as electrophysiology ( Eder et al, 2014 ), calcium cycle ( Stoehr et al, 2014 ), and metabolism and mitochondrial function ( Rhoden et al, 2022 ). Since adverse cardiac events are among the main causes for drug attrition ( Batta et al, 2020 ), new in vitro models like the EHT are sorely needed to predict such events in the early stages of drug development ( Pang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%